EFFECT OF PERIOPERATIVE EXERCISES ON KINESIOPHOBIA AND QUALITY OF LIFE IN PATIENTS UNDERGOING OPEN HEART SURGERY WITH FORWARD HEAD POSTURE - Aadil Omer; Azadeh Shadmehr; Waqar Ahmed Awan; Arshad Nawaz Malik; Maria Arif; Shafaq Altaf; Kainat Zaffar; Kazim Zaffar; Behrouz Attarbashi Moghadam (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
ABSTRACTOpen heart surgery is a major procedure that can significantly impact quality of life (QoL). Forward head posture (FHP) is a prevalent condition that also adversely affects QoL. Objective was to compare the effect of perioperative exercises on kinesiophobia and quality of life in persons undergoing open heart surgery (OHS) with forward head posture. This prospective, parallel-group, randomized controlled trial included 32 patients undergoing open heart surgery via median sternotomy with FHP, recruited from Rawalpindi Institute of Cardiology, Pakistan. Participants were randomized into two groups: 1) standard cardiac rehabilitation (CR) protocol, 2) CR protocol with therapeutic exercises for FHP. The intervention included a combination of stretching and strengthening exercises. Outcomes assessed were Health-related QoL (SF-36) and Tampa scale for Kinesiophobia (TSK); assessed at 4 weeks before surgery (T1), one day before surgery (T2), day of discharge (T3) & 4 weeks post-discharge (T4). One-way ANOVA and Repeated measures ANOVA were used to test hypotheses and evaluate changes from baseline to various time points. The between-group comparison indicated significant differences in TSK scores at all time points T1 (p = 0.029), T2 (p = 0.008), T3 (p = 0.001), and T4 (p = 0.022) while all domains of SF-36 showed no significant differences (p>0.05) at all time points. The study concludes that both standard CR and CR + therapeutic exercise for FHP showed equal effects on QoL of patients while kinesiophobia was greater in the group performing exercises for FHP.